Entrepreneurship, Innovative Education, and Cross-Sector Collaboration as Catalyst for Sustainable Health System in Nigeria - Isaac Msughter Peter; Velisiwe Gasa (GHMJ (Global Health Management Journal), 2026)
Background: The challenges of the health system are further exacerbated by the growing impacts of climate change, particularly in northern Nigeria. Climate change-related issues such as heat waves, flooding, and insurgency have worsened the burden of disease and highlighted vulnerabilities in health infrastructure and management structures. Aims: This study investigated entrepreneurship, innovative education, and cross-sector collaboration as catalysts for a sustainable health system in Nigeria. Methods: This study adopted a desk research design, sourcing data from Google Scholar, ERIC, JSTOR, Scopus, ResearchGate, and other websites. A total of 20 documents were identified and screened; 10 studies were finally selected because they were written in English, had a clear study purpose, were obtained from the identified sources, met the inclusion and exclusion criteria, and were used for analysis. Results: The study revealed that entrepreneurship contributes to the sustainability of the Nigerian Health System. Entrepreneurship in healthcare is considered the ability to bridge gaps in health service delivery through market-driven innovations that promote efficiency and responsiveness. The study also found that innovative education influences the sustainability of the health system. The study revealed that cross-sector collaboration catalyses a sustainable health system in Nigeria by introducing market-driven innovation, business practices that enhance health system resilience, improving coordination, and addressing social determinants of health that fall outside the purview of the conventional health sector. Conclusion: Entrepreneurship, innovative education, and cross-sector collaboration offer a feasible approach to developing a resilient and sustainable health system in Nigeria. When a good environment is created, it enables the promotion of entrepreneurship, innovation, partnerships, and health policies. This study suggests that Nigeria could strengthen the sustainability of its health system by implementing policies and initiatives that promote entrepreneurship, foster innovation in health education, and enhance cross-sector collaboration.